PERENCANAAN INTERIOR GRIYA SPA DAN KESEHATAN UNTUK IBU HAMIL DI BLITAR - Galang Sukmana; Putri Sekar Hapsari (Pendhapa, 2018)
ABSTRACT In general, spa spa planning and health for pregnant women in Blitar can generally be interpreted as planning activities of the inner space of a building that is the center of the whole body care activities aimed at mothers who are pregnant (pregnant). In addition to being used as a body treatment for spa, the spa is also expected to be able to interact or exchange experiences about pregnancy between pregnant women with one another or also between pregnant women and therapists on duty. Therefore the need for a body treatment such as a spa. In this work using several approaches, the approach includes the ergonomic approach to know the human dimension and everything related to the five human senses, and the theme or style approach that supports identity / coorporyte identity. This work takes the Mediterranean style with the concept of the park. This style and concept is applied to furniture and interior elements in the form of floors, walls, ceilings.Keywords: Spa interior, Mediterranean style, garden concept.